2018
DOI: 10.4196/kjpp.2018.22.2.203
|View full text |Cite
|
Sign up to set email alerts
|

Hypoxia-dependent mitochondrial fission regulates endothelial progenitor cell migration, invasion, and tube formation

Abstract: Tumor undergo uncontrolled, excessive proliferation leads to hypoxic microenvironment. To fulfill their demand for nutrient, and oxygen, tumor angiogenesis is required. Endothelial progenitor cells (EPCs) have been known to the main source of angiogenesis because of their potential to differentiation into endothelial cells. Therefore, understanding the mechanism of EPC-mediated angiogenesis in hypoxia is critical for development of cancer therapy. Recently, mitochondrial dynamics has emerged as a critical mech… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 31 publications
0
14
0
Order By: Relevance
“…2B), suggesting that only FLNa directly associates with Drp1. Dephosphorylation of Drp1 at Ser 637 participates in mitochondrial fission, and hypoxic stress induces dephosphorylation of Drp1 Ser 637 in on July 4, 2020 http://stke.sciencemag.org/ Downloaded from endothelial progenitor cells (40). We investigated whether the phosphorylation state at Ser 637 on Drp1 alters the interaction with FLNa.…”
Section: Drp1 Associates With Flna Under Hypoxiamentioning
confidence: 99%
“…2B), suggesting that only FLNa directly associates with Drp1. Dephosphorylation of Drp1 at Ser 637 participates in mitochondrial fission, and hypoxic stress induces dephosphorylation of Drp1 Ser 637 in on July 4, 2020 http://stke.sciencemag.org/ Downloaded from endothelial progenitor cells (40). We investigated whether the phosphorylation state at Ser 637 on Drp1 alters the interaction with FLNa.…”
Section: Drp1 Associates With Flna Under Hypoxiamentioning
confidence: 99%
“…Specifically, recent studies reported that hypoxia-induced mitochondrial fission via increased HIF-1α expression leading to increased DRP1 activity (57)(58)(59). This was indeed the case in the hippocampus of MHC-fed rats where increased DRP1 phosphorylation at Ser616 was observed.…”
Section: Discussionmentioning
confidence: 76%
“…Different microenvironments can have different effects on the proliferation and angiogenesis of EPCs. Kim et al (2018) found that a hypoxic microenvironment can promote proliferation, migration, and angiogenesis of human EPCs through mitochondrial division and related signaling pathways. However, Wu et al (2018) found that proliferation, migration, and angiogenesis of rat bone marrow-derived EPCs were inhibited in a high glucose micro-environment with hypoxia.…”
Section: Discussionmentioning
confidence: 99%